Event shapes in deep inelastic scattering at HERA - Chekanov, S; Derrick, M; Magill, S; Miglioranzi, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Pavel, N; Yagües Molina, A; Antonelli, S; et al. (2007)
Mean values and differential distributions of event-shape variables have been studied in neutral current deep inelastic scattering using an integrated luminosity of 82.2 pb-1 collected with the ZEUS detector at HERA. The kinematic range is 80 < Q2 < 20 480 GeV2 and 0.0024 < x < 0.6, where Q2 is the virtuality of the exchanged boson and x is the Bjorken variable. The data are compared with a model based on a combination of next-to-leading-order QCD calculations with next-to-leading-logarithm corrections and the Dokshitzer-Webber non-perturbative power corrections. The power-correction method provides a reasonable description of the data for all event-shape variables studied. Nevertheless, the lack of consistency of the determination of αs and of the non-perturbative parameter of the model, over(α0, -), suggests the importance of higher-order processes that are not yet included in the model. © 2006 Elsevier B.V. All rights reserved.